The Influence Of Brand Ambassador and Content Marketing on Gen Z Consumer Interaction Of Korean Spicy Chicken Sedaap Noodles in Surabaya - Shinta Kezia Apriliani; Sonja Andarini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
In digital era dominated by Gen Z, the right marketing strategy key to building relationships between brands and consumers. Mie Sedaap, through the Korean Spicy Chicken variant, takes advantage of Korean cultural trends among Gen Z by collaborating with brand ambassador Ahn Hyo Seop and implementing a content marketing strategy through social media. The objective is to analyze the influence of Brand Ambassadors and Content Marketing on Gen Z Consumer Interaction of Mie Sedaap Korean Spicy Chicken in Surabaya. This research applies this specific quantitative approach, utilizing an associative design, obtained from an online questionnaire via Google Forms for data collection and multiple SPSS was used to perform linear regression analysis. The sampling method applied is purposive sampling, totaling 164 respondents selected based on specific criteria consisting Gen Z who had seen advertisements, bought and consumed Mie Sedaap Korean Spicy Chicken in Surabaya.